2023
DOI: 10.3390/app13042719
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Load Forecasting of the Greek Electricity System

Abstract: Short-term load forecasting is an essential instrument in power system planning, operation, and control. It is involved in the scheduling of capacity dispatch, system reliability analysis, and maintenance planning for turbines and generators. Despite the high level of development of advanced types of machine learning models in commercial codes and platforms, the prediction accuracy needs further improvement, especially in certain short, problematic time periods. To this end, this paper employs public domain el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The authors suggested incorporating other economic indicators besides GDP that had a stronger correlation with electricity demand. Stamatellos and Stamatelos [12] suggested feed-forward neural networks for predicting electricity demand 24 h in advance for the Greek electricity system. The models incorporated important features such as the daily heating demands and cooling degree days in Athens, a representative location.…”
Section: Literature Review and Research Gap Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested incorporating other economic indicators besides GDP that had a stronger correlation with electricity demand. Stamatellos and Stamatelos [12] suggested feed-forward neural networks for predicting electricity demand 24 h in advance for the Greek electricity system. The models incorporated important features such as the daily heating demands and cooling degree days in Athens, a representative location.…”
Section: Literature Review and Research Gap Analysismentioning
confidence: 99%
“…[11] The limited data could not adequately train the model to forecast annual energy consumption for the UK. [12] Incorporating weather parameters such as air humidity and wind speed will be considered in the future.…”
Section: Long-term Energy Consumptionmentioning
confidence: 99%
“…Conversely, the research conducted by [19] introduces a weighting mechanism that considers factors such as the number of inhabitants, although a direct correlation with demand is not established. This approach is similarly adopted in [24], where load forecasting is conducted for the Greek System and meteorological variable weighting is performed, also taking into account the population of a large region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The remaining heating loads were covered by a heat pump [26]. Stamatellos et al examined the interactions between short-term electric car battery storage and long-term green hydrogen storage in a building [27]. Liu et al proposed a method for sizing the PV BESS system.…”
Section: Introductionmentioning
confidence: 99%